Given:
Nancy is running 3 meters per second.
Juan starts the same race 3 meters ahead of Nancy but he is going at 2 meters per second.
To find:
The equations for Nancy and Juan.
Solution:
Let x be the number of seconds.
Nancy is running 3 meters per second. So, the total distance covered by Nancy in the race is
![y=3x](https://tex.z-dn.net/?f=y%3D3x)
Juan starts the same race 3 meters ahead of Nancy but he is going at 2 meters per second. So, the total distance covered by Juan in the race is
![y=3+2x](https://tex.z-dn.net/?f=y%3D3%2B2x)
Therefore, the equations of Nancy and Juan are
and
respectively.
Answer: Area of rectangle can be given by expressions:
![(s-6)(s+1)\text {and }s^2-5s-6](https://tex.z-dn.net/?f=%28s-6%29%28s%2B1%29%5Ctext%20%7Band%20%7Ds%5E2-5s-6)
Step-by-step explanation:
Given : A square has sides of length s.
According to the question,
Dimensions of new rectangles=(s-6)×(s+1)
Thus, Area of rectangle= (s-6)×(s+1)
![=s^2-6s+s-6\\\Rightarrow\ s^2-5s-6](https://tex.z-dn.net/?f=%3Ds%5E2-6s%2Bs-6%5C%5C%5CRightarrow%5C%20s%5E2-5s-6)
Thus , area of rectangle can be given by expressions:
![(s-6)(s+1)\text {and }s^2-5s-6](https://tex.z-dn.net/?f=%28s-6%29%28s%2B1%29%5Ctext%20%7Band%20%7Ds%5E2-5s-6)
Answer:
1. 30 minutes
2. 15 minutes
3. 30 minutes
4. 60 minutes/ 1 hour
5. 45 minutes
Step-by-step explanation:
1. 60 - 45 = 15
15+15 = 30
2. 30 - 15 = 15
3. 45 - 15 = 30
4. 60 - 30 = 30
30 + 30 = 60
5. 60 - 15 = 45
Answer:
B
Step-by-step explanation:
its quadratic because it has the almost oval-ish shape
Answer: the fixed cost to rent the limousine is $200
Step-by-step explanation:
Let x represent the fixed cost rent the limousine.
Let y represent the cost of of hiring the driver of the limousine per hour.
It cost $500 to rent a limousine for 5 hours. This means that
x + 5y = 500 - - - - - - - - - - -1
It costs 800 to rent a limousine for 10 hours. This means that
x + 10y = 800 - - - - - - - - - - -2
Subtracting equation 2 from equation 1, it becomes
- 5y = - 300
y = - 300 /- 5
y = 60
Substituting y = 60 into equation 1, it becomes
x + 5 × 60 = 500
x + 300 = 500
x = 500 - 300
x = 200